PENERAPAN TERAPI BRAIN GYM PADA ANAK USIA PRASEKOLAH ( 4 TAHUN ) UNTUK MENURUNKAN TINGKAT KECEMASAN AKIBAT HOSPITALISASI D I R U A N G R AWA M E R TA RSUD KARAWANG - Wirdan Fauzi Rahman,; Yuli, Yuli; Siva Salsabila, (Journal of Innovation Research and Knowledge, 2024)
Hospitalization is a stressful experience for preschool-aged children due to limited cognitive and emotional abilities in understanding medical procedures. This condition often triggers anxiety that can affect the healing process and the child's cooperation during treatment. One non-pharmacological therapy that can help overcome anxiety is Brain Gym, a series of simple movements to stimulate the right and left brain functions, increase relaxation, and reduce emotional tension. This study aims to determine the effect of implementing Brain Gym therapy on reducing anxiety levels in preschool-aged children due to hospitalization in the Rawa Merta Ward, Karawang Regional Hospital. This study used a pre-experimental design with a one-group pre-test post-test design approach. A sample of 10 preschool children (aged 4 years) who underwent hospitalization was taken using purposive sampling. Anxiety levels were measured using a child anxiety level observation sheet (modified Wong-Baker Faces Anxiety Scale) before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of ρ <0.05. The average anxiety level of children before receiving Brain Gym therapy was 7.2 (severe anxiety category), while after the intervention it decreased to 3.8 (mild category). The Wilcoxon test showed a p-value of 0.004 (p < 0.05), indicating a significant effect of Brain Gym therapy on reducing anxiety levels in preschool children during hospitalization. Brain Gym therapy is effective in reducing anxiety levels in hospitalized preschool children. Nurses are advised to implement Brain Gym as a non-pharmacological intervention that is enjoyable, easy to perform, and can improve children's comfort during hospitalization